ANALISIS FAKTOR YANG MEMPENGARUHI KUALITAS TIDUR PADA LANSIA DENGAN DIABETES MELITUS TIPE 2 DI KOTA MALANG - Ika, Sri Sunaringsih; Putri, Peni Julia; Yuliadarwati, Nungki Marlian (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
In general, people with diabetes mellitus have trouble concentrating on sleeping well because they often want to urinate as a result of increased blood sugar levels. The purpose of this study was to analyze what factors affect sleep quality in elderly people with type 2 diabetes mellitus. The research method used a cross-sectional approach. Respondents consisted of 35 respondents with a sampling technique using purposive sampling. Measurements were carried out using the PSQI questionnaire (Pittsburgh Sleep Quality Index), (PSS) Perceived Stress Scale, and Sociodemographic sheets. The results of multiple linear analysis tests obtained significant values ​​for age (0.041), duration of DM (0.037), co-morbidities (0.012), and psychological factors (0.027). In conclusion, the results of this study indicate that there are factors, namely age, duration of DM, comorbidities, and psychological factors that affect sleep quality in elderly people with type 2 diabetes mellitus.